2018
DOI: 10.2521/jswtb.54.65
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Detection of Pathogenic Bacteria in Jar Water, Community Well Groundwater, and Environmental Water in the Kathmandu Valley, Nepal

Abstract: Microbial contamination of water sources remains a serious problem in the Kathmandu Valley, Nepal. This study was conducted to comprehensively investigate the occurrence of pathogenic bacteria in water samples collected from the valley, most of which were used for drinking and other domestic purposes. The water samples consisted of 10 samples of commercial jar water, 10 of groundwater from shallow dug wells, 3 of groundwater from deep tube wells, 1 of stone spout water, 2 of spring water, and 2 of river water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…'%' indicates presence of bacteria in samples divided by total number of samples collected.A classification at the genus level revealed that 12 generaPseudomonas, and Xanthomonas) were present in 15 (94%) of the 16 samples tested. This result was comparable to that of a previous study, where genera such as Acinetobacter, Arthrobacter, Brevibacterium, Legionella, and Pseudomonas, were detected in 82% (23/28) of water samples, which had been collected in 2014[27]. Waterborne pathogenic bacteria that could be transmitted through the fecal-oral route were identified, whereby Vibrio cholerae, Klebsiella spp., and Salmonella enterica serovars were detected in 63%, 38%, and 31% of the water samples tested, respectively.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…'%' indicates presence of bacteria in samples divided by total number of samples collected.A classification at the genus level revealed that 12 generaPseudomonas, and Xanthomonas) were present in 15 (94%) of the 16 samples tested. This result was comparable to that of a previous study, where genera such as Acinetobacter, Arthrobacter, Brevibacterium, Legionella, and Pseudomonas, were detected in 82% (23/28) of water samples, which had been collected in 2014[27]. Waterborne pathogenic bacteria that could be transmitted through the fecal-oral route were identified, whereby Vibrio cholerae, Klebsiella spp., and Salmonella enterica serovars were detected in 63%, 38%, and 31% of the water samples tested, respectively.…”
supporting
confidence: 87%
“…People use 12% and 22% of groundwater for drinking and cooking purpose [1]. A previous study of groundwater and river water revealed 5 BSL 3 pathogens, of which the Anaplasma marginale/centrale group (39%) was detected most frequently [27]. In this study, 6 BSL 3 pathogens were detected from different water samples, and the detection ratio of the A. marginale/centrale group (94%) was the highest (Table 1).…”
Section: Occurrence Of Pathogenic Bacteria In Water Samplessupporting
confidence: 50%
See 1 more Smart Citation